Optimal concentration of nanostructured powder in protective gas - Barannikova S. A. Svetlana Aleksandrovna; Shlyakhova G. V. Galina Vitaljevna; Zernin E. A. Evgeny Aleksandrovich; Kuznetsov M. A. Maksim Aleksandrovich (2017, 2017)
Title screen